Isolation of Limosilactobacillus mucosae G01 with inhibitory effects on porcine epidemic diarrhea virus in vitro from Bama pig gastroenteritis - Zhang, Bin; Shen, Haiyan; Gou, Hongchao; Wuri, Nile; Zhang, Chunhong; Liu, Zhicheng; He, Haiyan; Nie, Jingjing; Qu, Yunzhi; Geri, Letu; Zhang, Jianfeng (Frontiers in Microbiology, 2024)
Porcine epidemic diarrhea virus (PEDV) is responsible for causing fatal watery diarrhea in piglets, resulting in significant economic losses within the pig farming industry. Although vaccination is currently employed as a preventive measure, certain vaccines do not provide complete protection against PEDV field strains. Probiotics present a promising alternative due to their ability to regulate intestinal flora, enhance host immunity, and improve resistance against pathogenic microorganisms.We isolated six lactic acid bacteria (LAB) from the fecal microorganisms of Bama pigs, compared to Limosilactobacillus mucosae DSM13345 of the same genus in which Limosilactobacillus mucosae G01 (L.mucosae G01) proved to have a potent anti-PEDV effect. In a comprehensive manner, L.mucosae G01 significantly augmented the phosphorylation of IRF3 in IPEC-J2 cells, resulting in the induction of interferons (IFN α, IFN β, IFN λ1, and IFN λ3) and subsequent upregulation of interferon-stimulated genes (ISGs) (MX1, MX2, OAS1, and ZAP) in a dose-dependent fashion, consequently leading to the mitigation of PEDV replication. These findings underscore the promising prospects of L.mucosae G01 as a naturally derived substitute for combating PEDV and other enteric coronavirus infections.